Evaluation of the Magnitudes of Force and Patterns for the Intrusion of Maxillary First Molar Teeth with Mini-Screw Anchorage, Analyzed Using the Finite Element Method - Pheerawanitchakun, Phanisa; Patanaporn, Virush; Rungsiyakull, Chaiy (Chiang Mai Dental Journal, 2018)
The purposes of this study were to evaluate the greatest magnitude of force that can be applied in order to initiate the intrusion of maxillary first molar teeth without exceeding the periodontal capillaryvessel blood pressure of 0.0047 MPa and to compare the use of anchorage from either two or three miniscrews to determine the optimal pattern of force for the intrusion of maxillary first molar teeth, using the finite element method. A three-dimensional finite element model was constructed using SolidWorks software. Intrusive force was applied at the middle of the occlusal surface of the maxillary first molar tooth. The finite element model was able to determine the greatest magnitude of force applied by simulation of various force magnitudes. To determine the optimal pattern of force, the different patterns of stress distribution and initial displacements of maxillary first molar teeth between the pattern of intrusion using two and three mini-screws were compared using ABAQUS software. In the pattern of intrusion using two mini-screws, on the buccal side, a mini-screw was placed between the roots of the first and second molar teeth. On the palatal side, a mini-screw was placed between the roots of the second premolar and first molar teeth. In the pattern of intrusion using three mini-screws, two mini-screws were inserted into the maxillary buccal alveolar bone, one between the roots of the second premolar and first molar teeth and the other between the roots of the first and second molar teeth. The third mini-screw, in the mid-palatal suture, supplied the palatal anchorage. In the case of each pattern, the calculated magnitude of forces was applied to each maxillary first molar tooth. Results showed that the greatest magnitude of force for the intrusion of maxillary first molar teeth was 13 grams. It was concluded that the pattern with two miniscrews was the optimal pattern of force for the intrusion of the maxillary first molar because this pattern provided more bodily movement than that with three mini-screws.